2018
DOI: 10.1021/acs.chemmater.8b00676
|View full text |Cite
|
Sign up to set email alerts
|

A-Site Cation in Inorganic A3Sb2I9 Perovskite Influences Structural Dimensionality, Exciton Binding Energy, and Solar Cell Performance

Abstract: Inspired by the rapid rise in efficiencies of lead halide perovskite (LHP) solar cells, lead-free alternatives are attracting increasing attention. In this work, we study the photovoltaic potential of solution-processed antimony (Sb)-based compounds with the formula A 3Sb2I9 (A = Cs, Rb, and K). We experimentally determine bandgap magnitude and type, structure, carrier lifetime, exciton binding energy, film morphology, and photovoltaic device performance. We use density functional theory to compute the equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
161
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(170 citation statements)
references
References 41 publications
8
161
1
Order By: Relevance
“…The experimental and theoretical work on Cs 3 Sb 2 I 9 shows that this material possesses a layered 2D structure with a direct bandgap of 2 eV, suggesting a suitable material for photovoltaics. The preferred formation of 0D and 2D structure depends on the sample preparation technique as well as an addition of additives ,,. The bulk phase of Sb based perovskites are explored in the specific form of Cs 3 Sb 2 Cl 9 (hexagonal P321), Cs 3 Sb 2 Br 9 (trigonal P3m1 ), MA 3 Sb 2 I 9 (hexagonal P 6 3 / mmc ), MA 3 Sb 2 Br 9 (trigonal P3m1 ) and (NH 4 ) 3 Sb 2 I x Br 9− x (0≤ x ≤9) (Monoclinic P121/n1) ,.…”
Section: Antimony Perovskitesmentioning
confidence: 95%
“…The experimental and theoretical work on Cs 3 Sb 2 I 9 shows that this material possesses a layered 2D structure with a direct bandgap of 2 eV, suggesting a suitable material for photovoltaics. The preferred formation of 0D and 2D structure depends on the sample preparation technique as well as an addition of additives ,,. The bulk phase of Sb based perovskites are explored in the specific form of Cs 3 Sb 2 Cl 9 (hexagonal P321), Cs 3 Sb 2 Br 9 (trigonal P3m1 ), MA 3 Sb 2 I 9 (hexagonal P 6 3 / mmc ), MA 3 Sb 2 Br 9 (trigonal P3m1 ) and (NH 4 ) 3 Sb 2 I x Br 9− x (0≤ x ≤9) (Monoclinic P121/n1) ,.…”
Section: Antimony Perovskitesmentioning
confidence: 95%
“…[120] The VBM consists mainly of I 5p orbitals slightly hybridized with Bi 6s orbitals, while the CBM is derived from the antibonding states of Bi 6p and I 5p orbitals. [118,[123][124][125][126] Figure 11c shows the Tauc plot of Cs 3 Bi 2 I 9 crystals at 10 K. Notably, the sharp excitonic peak at 2.56 eV is well separated from the electronic bandgap at 2.86 eV, corresponding to an excitonic binding energy, E b X = 300 meV. [118,121,122] The 0D structure also causes large exciton binding energies.…”
Section: A 3 B(iii) 2 X 9 Nonperovskites (Dimer Phases)mentioning
confidence: 99%
“…Taking Cs 3 Bi 2 I 9 (Figure 11a) as an example, the calculations using hybrid Heyd-Scuseria-Ernzerhof (HSE) [119] functional with SOC indicated that Cs 3 Bi 2 I 9 exhibits an indirect bandgap of 2.10 eV from the Γ point to the K point (Figure 11b). [118,121,122] The 0D structure also causes large exciton binding energies. Because of the isolation of [Bi 2 I 9 ] bioctahedra, both the VBM and the CBM are relatively localized, leading to large carrier effective masses.…”
Section: A 3 B(iii) 2 X 9 Nonperovskites (Dimer Phases)mentioning
confidence: 99%
“…Investigations to replace lead in 2D PSCs focused on the use of layered bismuth [52]‐ and antimony‐based perovskites . Unlike most of the others “B‐site” metals discussed in this Minireview, antimony and bismuth have predominantly a 3+ oxidation state, which precludes the formation of traditional 3D halide perovskites with these metals.…”
Section: Lead‐free 2d Perovskites In Solar Cellsmentioning
confidence: 99%